Impact of COVID-19 Lockdown in Eating Disorders: A Multicentre Collaborative International Study - Baenas, Isabel; Etxandi, Mikel; Munguía, Lucero; Granero, Roser; Mestre-Bach, Gemma; Sánchez, Isabel; Ortega, Emilio; Andreu, Alba; Moize, Violeta L; Fernández-Real, Jose-Manuel; Tinahones, Francisco J; Diéguez, Carlos; et al. (Nutrients, 2021)
BACKGROUND: The COVID-19 lockdown has had a significant impact on mental health. Patients with eating disorders (ED) have been particularly vulnerable. AIMS: (1) To explore changes in eating-related symptoms and general psychopathology during lockdown in patients with an ED from various European and Asian countries; and (2) to assess differences related to diagnostic ED subtypes, age, and geography. METHODS: The sample comprised 829 participants, diagnosed with an ED according to DSM-5 criteria from specialized ED units in Europe and Asia. Participants were assessed using the COVID-19 Isolation Scale (CIES). RESULTS: Patients with binge eating disorder (BED) experienced the highest impact on weight and ED symptoms in comparison with other ED subtypes during lockdown, whereas individuals with other specified feeding and eating disorders (OFSED) had greater deterioration in general psychological functioning than subjects with other ED subtypes. Finally, Asian and younger individuals appeared to be more resilient. CONCLUSIONS: The psychopathological changes in ED patients during the COVID-19 lockdown varied by cultural context and individual variation in age and ED diagnosis. Clinical services may need to target preventive measures and adapt therapeutic approaches for the most vulnerable patients.
Keywords: Adolescent; Europe; Adult; Male; Asia; lidé; longitudinální studie; Humans; Child; Evropa; Asie; karanténa; COVID-19; poruchy příjmu potravy; Young Adult; COVID-19 Isolation Eating Scale (CIES); eating symptoms; psychological impact; mužské pohlaví; SARS-CoV-2; Quarantine; internacionalita; dospělí; eating disorders; mladý dospělý; Social Isolation; dítě; sociální izolace; ženské pohlaví; mladiství; Female; Internationality; Feeding and Eating Disorders; COVID-19 lockdown; Longitudinal Studies